UPAYA MENINGKATKAN SIKAP PEDULI TERHADAPSESAMADENGAN MENGGUNAKAN MODEL PEMBELAJARANKONSIDERASI PADA MATA PELAJARAN AKIDAHAKHLAK SISWA KELAS IX MTSKASRATUSSA’ADAH - Sonya Elsa Triyanda Pohan; Marhan Hasibuan; Anida Anida (Jurnal Iqtirahaat, 2023)
The problems are the lack of awareness of students to protect the school environment, lack of harmony between each other, there are still students who speak when the teacher explains and the lack of awareness of students in complying with the rules that apply at school. This research is a class action research (CAR) carried out in two cycles, where each cycle consists of four stages, namely planning, acting, observing and reflecting. Using qualitative descriptive analysis techniques. The subjects of this study were 28 class IX students at MTs Kasratussa'adah. The results of the research in cycle I, the average student questionnaire results increased by 2.93 from the implementation of the pre-cycle. It is known that as many as 23 students (82.14%) are in the high category and the remaining 5 students (17.86%) are in the medium category. Because the researcher felt that these results had not reached the success criteria so that cycle II was carried out, in this action there was another increase, namely it was known that only 1 student (3.57%) was in the medium category and the remaining 27 students (96.43%) were in the high category. This shows that the consideration learning model that the researcher uses is able to increase students' caring attitude towards others, especially in the Aqidah Akhlak subject, even though it is not 100%.